2021
DOI: 10.1111/dth.14881
|View full text |Cite
|
Sign up to set email alerts
|

Autologous intralesional platelet rich plasma improves melasma

Abstract: Platelet rich plasma (PRP) is an upcoming interventional therapy for the treatment of melasma. Its efficacy is due to the multiple growth factors present in it which decrease melanogenesis by various signal transduction pathways. The present study evaluated the efficacy of PRP as a standalone agent in treatment of melasma. This is an open labeled prospective trial. Forty patients were given intralesional PRP at once monthly interval. Three such PRP sessions were carried out and the patients were followed up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
4
18
0
1
Order By: Relevance
“…A further four articles were excluded for the lack of essential information. Ultimately, ten studies were included in the data integration for MASI scores and subjective evaluation [19][20][21][22][23][24][25][26][27][28]. The inclusion and exclusion process of the studies is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further four articles were excluded for the lack of essential information. Ultimately, ten studies were included in the data integration for MASI scores and subjective evaluation [19][20][21][22][23][24][25][26][27][28]. The inclusion and exclusion process of the studies is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…The year of publication ranged from 2018 to 2021. In terms of study design, there were four RCTs [19][20][21][22], three split-face trials [23,24,27] and three self-controlled trials [25,26,28]. Thelocations of these trials were China (3 trials), India (2 trials), Egypt (3 trials), Thailand (1 trial) and Pakistan (1 trial).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Being autologous, the adverse effects of PRP therapy are rare and minimal which include pain in the injected area, infection, skin discoloration, allergic reaction, and blood clot formation 29 . The mitogenic effects of PRP are only limited to augmentation of the normal healing process and is theoretically not mutagenic, as the growth factors released do not enter the cell or its nucleus, but only bind to the membrane receptors and induce signal transduction mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…TGF decreases melanogenesis by downregulating microphthalmia-associated transcription factor promoter activity and inhibiting the expression of paired-box homeo-c gene (PAX 3), which at the protein level, reduces the production of tyrosinase and tyrosinase-related protein 1 and 2. [9] EGF inhibits prostaglandin-E2 expression and tyrosinase enzyme activity. [10] PRP can be used stand alone and with microneedling, radiofrequency, and lasers.…”
Section: Complicated Melasma With Rosacea and Acnementioning
confidence: 99%